Teaching Foreign Languages to Young Learners in Ukraine: Pages of History (Training and Practice : Journal of Educational Sciences, 2017)
This article represents a brief overview of the history of early language education in Ukraine. It starts with the period of the Russian Empire, when skills in foreign languages were valued as a mark of a privileged social status and an integral part of the liberal arts education curriculum in gymnasiums. Then it goes on with the primary language education of the Soviet period, starting with the late 1940s when the idea of an ‘early-start’ in teaching foreign languages to young schoolers was introduced on the state level, and first schools with a number of subjects instructed in a foreign language were set up. It also focuses on the experimental teaching of foreign languages to 4-6-years-old children in the 1960s and 1980s. The author completes with the account of changes in the early language education in Ukraine in the post-Soviet period, when this practice became regular in primary schools. Issues of training teachers of foreign languages for kindergartens and primary schools are also shortly covered.